Analysis of Superior Commodity Production, Food Access, and Institutional Roles Towards Sustainable Food Security in Sungai Penuh City: Analysis of Superior Commodity Production, Food Access, and Institutional Roles Towards Sustainable Food Security in Sungai Penuh City - Rahayu, Silvia; Ernita, Dewi; Nanda Putri, Anjelia (Qawwam : The Leader's Writing, 2026)
. This study aims to analyze the influence of superior commodity production, food access, and institutional roles on sustainable food security in Sungai Penuh City, an agricultural city in Jambi Province, 59.2% of which is the Kerinci Seblat National Park (TNKS). With its hilly topography and limited urban land area, efforts to achieve food security face unique challenges. The research method uses a quantitative approach with the Two-Stage Least Squares (TSLS) analysis tool through E-Views software. Primary data were obtained from questionnaires to 396 respondents spread across 8 sub-districts, supported by secondary data from the Central Statistics Agency and the local Food Security Office. The results showed that simultaneously, the three independent variables had a significant effect and were able to explain 83.83% of the variation in sustainable food security (R-squared = 0.8383). Partially, institutional roles had the most dominant influence (coefficient 0.162), followed by superior commodity production (0.126), and food access (0.045). The leading commodity of lowland rice serves as the backbone of local food security, while food access is improved through affordable market programs and food kiosks. Institutions play a key role through programs such as the Food Brigade, the Food Reserves Regulation, and the Bagizi Food Kitchen (MBG). It was concluded that achieving sustainable food security in Sungai Penuh City requires an integrated approach that strengthens institutional capacity, optimizes production of leading commodities on limited land, and ensures stable and affordable food access for all.